Analisis Penggunaan Aplikasi Brimen Terhadap Kemudahan Kinerja Petugas Administrasi Kredit (ADK) PT Bank Rakyat Indonesia (PERSERO) Tbk Kantor Cabang Pasuruan - Wisnu Erlangga; Mya Hayda Karisma; Jihan Fita Nabila; M.F. Hidayatullah (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
This research aims to analyze the usage of the BRIMEN application and its impact on the ease of performance of Credit Administration Officers (ADK) at the Pasuruan Branch Office of PT Bank Rakyat Indonesia (Persero) Tbk. The research method used is qualitative method with a participatory approach and descriptive research type. Data were obtained through observation, interviews, and direct documentation in the field. The results show that the BRIMEN application facilitates ADK officers in various tasks such as scanning customer documents, uploading files to the system, and archiving physical files. Although still in the refinement stage, BRIMEN provides time efficiency and flexibility for officers, who previously performed processes manually. In conclusion, BRIMEN has provided benefits in improving the work efficiency of Credit Administration Officers (ADK) at the Pasuruan Branch Office. Although further refinement is needed, this application has the potential to be continuously developed to enhance productivity and operational efficiency.